2021
DOI: 10.1007/s10865-021-00243-9
|View full text |Cite
|
Sign up to set email alerts
|

Why some parents made firearms more accessible during the beginning of the COVID-19 pandemic: results from a national study

Abstract: and the unknown; and (4) Easier access and greater protection, threat unspecified. Some parents-largely motivated by fear-chose to store firearms in a more accessible manner during the beginning of the COVID-19 pandemic to protect their family against possible external threats. Understanding the fear that motivates parents' decisions regarding storage practices might aid interventions focused on harm reduction and safer storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This is in contrast to many parent's perceptions regarding their child's involvement with firearms in the home [21] . Another recent report revealed that fears of protests, potential home invasion, and a general sense of the “unknown” associated with the onset of the pandemic caused parents to make firearms more accessible to their adolescent children [22] . Increased time at home coupled with increased rates of firearm purchase, a rise in access to weapons kept at home, and unsafe firearm storage practices likely contributed to the increase in unintentional firearm injuries compared to other injury intents seen in adolescents in Colorado following the onset of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to many parent's perceptions regarding their child's involvement with firearms in the home [21] . Another recent report revealed that fears of protests, potential home invasion, and a general sense of the “unknown” associated with the onset of the pandemic caused parents to make firearms more accessible to their adolescent children [22] . Increased time at home coupled with increased rates of firearm purchase, a rise in access to weapons kept at home, and unsafe firearm storage practices likely contributed to the increase in unintentional firearm injuries compared to other injury intents seen in adolescents in Colorado following the onset of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The downstream consequences of the COVID-19 pandemic and SHO have yet to be completely understood; however, as fear, mistrust, and uncertainty increased, many individuals obtained firearms for protection [ 19 , 20 ]. There was an unprecedented surge in US gun and ammunition sales in 2020, often by first-time buyers who may also be less likely to know how to safely use, secure and store weapons [ 3 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was an unprecedented surge in US gun and ammunition sales in 2020, often by first-time buyers who may also be less likely to know how to safely use, secure and store weapons [ 3 , 19 , 21 ]. Additionally, some parents reported that fear of protests, home invasion, or the unknown caused them to make firearms more accessible to their adolescent children [20] .…”
Section: Discussionmentioning
confidence: 99%
“…unlocked 23 . A survey of firearm-owning parents found that a minority, 5%, intentionally made their firearms more accessible during the pandemic, most commonly due to concern for increased civil unrest or riots 24 . Rising firearm purchases are correlated with increases in unintentional firearm deaths, and in particular, has been associated with a rising rate of unintentional deaths due firearms among children aged 1-4 years old 25 .…”
Section: Discussionmentioning
confidence: 99%